African-American Sexual Minority Adolescents and Sexual Health Disparities: An Exploratory Cross-Sectional Study - Norris, Alyssa L. (J Natl Med Assoc, 2018)
PURPOSE. To better understand sexual health disparities among African-American sexual minority adolescents. METHODS. African-American adolescents (N = 1,120; mean age = 15.24 years) were recruited from 4 cities (Columbia, SC; Macon, GA; Providence, RI; Syracuse, NY) to a larger trial. The current analyses used data from the 18-month follow-up when adolescents reported on their sexual partnerships, condom use knowledge, self-efficacy and outcome expectancies for condom use, sexual risk behavior, and STI testing history. RESULTS. Compared with heterosexual adolescents, sexual minority adolescents reported more concerns about potential relationship harms resulting from safer sex negotiation. Sexual minority adolescents were also more likely to engage in riskier sexual behaviors, with females reporting more sexual partners and drug use prior to sex, and males reporting inconsistent condom use and higher rates of HIV. CONCLUSIONS. African-American sexual minority adolescents evidence disparities in sexual risk behavior and STI history that appear to result from interpersonal and relationship concerns. These concerns need to be targeted in sexual health interventions for sexual minority adolescents.